Outcomes of integrating a clinical pharmacist in the pediatric cardiology ward - Elhabil, Mohammed Kamel; Yousif, Mirghani; Eldalo, Ahmed Salah; Ahmed, Kannan O.; Abunada, Mohamed Ibrahim (African Pharmaceutical Journal, 2022)
To date, very limited data are available on clinical pharmacist's services in pediatric cardiology. The aim of this review was to assess "drug-related problems" (DRPs) and patient outcomes during the involvement of the clinical pharmacist in the pediatric cardiology ward. Studies published between January 2000 and November 2021 were searched across Medline, PubMed, Google Scholar, Elsevier, and ScienceDirect for “DRPs” and “patient outcome” with “clinical pharmacist” and “pediatric cardiology”. Results revealed that the incorporation of clinical pharmacists in the multidisciplinary team can detect and resolve DRPs, reduce the overall burden of healthcare costs, and improve drug safety in pediatric cardiology patients. Most DRPs identified and interventions proposed by the clinical pharmacists were accepted by the physicians. Studies have also reported a positive impact on patient outcomes, including: shorter hospital stay, fewer disease events, optimal anticoagulation levels, lipid levels, and blood pressure. Moreover; pharmacist-led discharge medication counseling resulted in better medication adherence, fewer medication discrepancies, and a lower incidence of cardiovascular-associated hospital readmissions. In summary, there is growing evidence that integration and interventions of clinical pharmacists into cardiology ward has a positive influence on DRPs and patient outcomes.